(untitled) (CIPEEX, 2025)
Against the backdrop of a digitalised world, financial institutions have sought technological innovations in order to meet the needs of an increasingly connected society, with security being a critical factor that users consider when choosing financial services. This study presents an integrative literature review on the relationship between technological innovations and security in financial institutions, with a bibliographical, exploratory and qualitative approach. The research in question aimed to evaluate and discuss the perception of security among users of financial applications, in order to observe their experience of technological innovations. The literature was analysed by searching the Scielo, Periódicos da Capes and Scopus databases, selecting articles published in Portuguese and English and classifying studies with a predominance of the central theme for the extraction and discussion of the results found, considering the publication period between 2020 and 2024 and using the descriptors banks, digital, security and users, with the application of the Boolean indicators and or. Articles whose subject matter was not aligned with the topic covered in this research were also excluded. After applying these criteria, the final result was a total of 11 studies selected for analysis. The analysis showed that the availability of digital tools that allow users to conveniently carry out a wide range of financial transactions has, on the other hand, led to a high level of concern about security, which is a critical factor that users consider when choosing financial services, demonstrating a growing awareness of the importance of protecting data and financial transactions. In this way, the financial institutions themselves are aware of the possible weaknesses and are investing in a process to make customers aware of security. This shows an effort to educate and train users on how to protect their personal data and carry out financial transactions correctly, in order to mitigate the perceived risks, since the evolution of the payments and banking services market has accelerated banking, allowing more users to have access to financial services. In view of this, the use of these tools has made security crucial, since cybersecurity-related risks represent a major concern, considering the financial and personal consequences that can be caused to users who suffer from data leaks. It is therefore essential that financial institutions invest more in guaranteeing the privacy and security of their customers’ data. The research highlights the growing importance of security amid technological innovations in the financial sector. This makes measures such as user awareness and investments by financial institutions in security measures essential, with the aim of guaranteeing customer trust and protecting their data in the constantly evolving digital environment.